SPECIFIC CHARACTERISTICS AND PREVALENCE OF MENTAL DISORDERS IN ONCOLOGICAL DISEASES OF THE LUNG AND GASTROINTESTINAL TRACT - Rustamov U.T. (Ustozlar uchun, 2025)
Abstract:Mental disorders are more common in cancer patients than other somatic diseases, which reduces their flexibility and the quality of rehabilitation. The article describes the clinical characteristics of mental disorders in patients with various oncological diseases (lung, gastrointestinal tract cancer).